1998
DOI: 10.1136/bmj.316.7136.969
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of heparin in peripheral venous and arterial catheters: systematic review and meta-analysis of randomised controlled trials

Abstract: Conclusions: Use of intermittent heparin flushes at doses of 10 U/ml in peripheral venous catheters locked between use had no benefit over normal saline flush. Infusion of low dose heparin through a peripheral arterial catheter prolonged the duration of patency but further study is needed to establish its benefit for peripheral venous catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(77 citation statements)
references
References 34 publications
7
63
1
6
Order By: Relevance
“…220 In addition, there is a reported association between thrombosis and peripherally inserted catheter-associated bloodstream infection in neonates (n=882 neonates, 1540 peripherally inserted catheters; P<0.05). 221 Although not reported, likely because of low numbers, there may also be an increased risk of shunt thrombosis in neonates with infection.…”
Section: Incidence Prevention and Treatment Of Thrombosis In Childrmentioning
confidence: 99%
“…220 In addition, there is a reported association between thrombosis and peripherally inserted catheter-associated bloodstream infection in neonates (n=882 neonates, 1540 peripherally inserted catheters; P<0.05). 221 Although not reported, likely because of low numbers, there may also be an increased risk of shunt thrombosis in neonates with infection.…”
Section: Incidence Prevention and Treatment Of Thrombosis In Childrmentioning
confidence: 99%
“…12 Another possible explanation is the evidence that heparin and physiological saline are associated with similar rates of thrombosis for shorter length peripheral venous and arterial catheters with shorter dwell times. 6 Last, the recommended use of a heparin solution rather than saline for flushing is considered inconclusive in guidelines for maintenance of short-term CVCs. 3 The percentage of respondents who used heparin-containing flush solutions was higher for the 64 advanced practice nurses (clinical nurse specialists, nurse practitioners, or educators) than for the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Care of peripherally placed central catheters, introducer sheaths, and dialysis catheters was excluded because practice patterns and guidelines vary with different types of catheters. [3][4][5][6][7][8] In addition, one of the authors (D.P.) is a member of a 13-hospital system intravenous products committee and therefore had extensive knowledge of the various needleless devices available on the market, knowledge that contributed to the face validity of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…2 One meta-analysis performed in 1998 demonstrated an increased longevity of lines flushed with HS. 7 This included one of the largest studies to date -a multicentre unblinded randomised control trial from the American Association of Critical Care Nurses. The study of 5139 subjects concluded that HS lines had a higher probability of remaining patent, compared to those flushed with NS.…”
Section: Discussionmentioning
confidence: 99%